Impact of primary healthcare providers’ initial role security and therapeutic commitment on implementing brief interventions in managing risky alcohol consumption: a cluster randomised factorial trial - Keurhorst, Myrna N.; Wensing, Michel (Implementation science, 2016)
Brief interventions in primary healthcare are cost-effective in reducing drinking problems but poorly implemented in routine practice. Although evidence about implementing brief interventions is growing, knowledge is limited with regard to impact of initial role security and therapeutic commitment on brief intervention implementation.